PENINGKATAN KUALITAS BELAJAR MATEMATIKA SISWA SMA PADAMU NEGERI MELALUI QUIPPER VIDEO - Ropinus Sidabutar (JGK (Jurnal Guru Kita), 2023)
The purpose of this research is to create a mathematics learning technique to make it more interesting and also fun by carrying out online tutoring based on Quipper Video. This study uses qualitative methods with descriptive analysis. The research was conducted at Padamu Negeri Medan High School which carried out online tutoring. The results of this study are, (1) There is an increase in the quality of students' mathematics learning in the aspects of results, motivation, and aspects of the lesson plan. (2) The "Quipper Video" learning model has a positive impact on students' mathematics learning outcomes. (3) Students as research objects are excited and actively participate in mathematics learning activities through Quipper Video. (4) One of the supporting factors in creating Quipper Video online-based mathematics learning is a computer or android (5) Low motivation and lack of facilities also become inhibiting factors in the Quipper Video online-based mathematics learning process.